Viral load decrease in SARS‐CoV‐2 BA.1 and BA.2 Omicron sublineages infection after treatment with monoclonal antibodies and direct antiviral agents. Issue 1 (7th October 2022) - Mazzotta, Valentina; Cozzi Lepri, Alessandro; Colavita, Francesca; Rosati, Silvia; Lalle, Eleonora; Cimaglia, Claudia; Paulicelli, Jessica; Mastrorosa, Ilaria; Vita, Serena; Fabeni, Lavinia; Vergori, Alessandra; Maffongelli, Gaetano; et al.
Abstract: The efficacy on the Omicron variant of the approved early coronavirus disease‐2019 (COVID‐19) therapies, especially monoclonal antibodies, has been challenged by in vitro neutralization data, while data on in vivo antiviral activity are lacking. We assessed potential decrease from Day 1 to Day 7 viral load (VL) in nasopharyngeal swabs of outpatients receiving Sotrovimab, Molnupiravir, Remdesivir, or Nirmatrelvir/ritonavir for mild‐to‐moderate COVID‐19 due to sublineages BA.1 or BA.2, and average treatment effect by weighted marginal linear regression models. A total of 521 patients (378 BA.1 [73%], 143 [27%] BA.2) received treatments (Sotrovimab 202, Molnupiravir 117, Nirmatrelvir/ritonavir 84, and Remdesivir 118): median age 66 years, 90% vaccinated, median time from symptoms onset 3 days. Day 1 mean VL was 4.12 log2 (4.16 for BA.1 and 4.01 for BA.2). The adjusted analysis showed that Nirmatrelvir/ritonavir significantly reduced VL compared to all the other drugs, except versus Molnupiravir in BA.2. Molnupiravir was superior to Remdesivir in both BA.1 and BA.2, and to Sotrovimab in BA.2. Sotrovimab had better activity than Remdesivir only against BA.1. Nirmatrelvir/ritonavir showed the greatest antiviral activity against Omicron variant, comparable to Molnupiravir only in the BA.2 subgroup. VL decrease could be a valuable surrogate of drug activity in the context of the high prevalence of vaccinated people and low probability of hospital admission.